Political Uncertainty and Financial Firm Performance: Evidence from the Thai Economy as an Emerging Market in Asia - Worraphan Trakarnsirinont; Wisuttorn Jitaree; Wonlop Writthym Buachoom (Economies, 2023)
This study analyzes the effects that certain political-uncertainty factors have on financial firm performance in the Stock Exchange of Thailand (SET). The results of a panel regression performed on a database of 7976 firm-years over 18-year unbalanced panel data from 2001 to 2018 show a mixed relationship between political uncertainty and firm performance. The constitutional reform harms the return on assets (ROA), and the government election and political protest significantly decreased the market value of equity (MVE). In contrast, constitutional reform increased MVE, and the government election positively impacted ROA. Therefore, this study emphasizes how political unpredictability is assumed to influence firm performance in Thailand’s economy, an Asian developing country.
Keywords: Market Dynamics and Volatility; Corporate Finance and Governance; Financial Markets and Investment Strategies